USABILITY TESTING LEARNING MANAGEMENT SYSTEM (LMS) BERBASIS MOODLE DI SMA NEGERI 1 SUKAWATI - A.A Istri Ita Paramitha; Eka Grana Aristyana Dewi; Ni Luh Aristya Dewi (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
E-Learning is a medium that supports virtual learning activities using electronic devices such as computers. SMA Negeri 1 Sukawati is one of the public schools in Bali that uses Moodle-based LMS to support e-learning activities. Based on the results of direct observations accompanied by unstructured interviews that researchers did, it was found that there were still many shortcomings in the LMS. Therefore, this study will measure the Usability aspect of the LMS using the PSSUQ method. PSSUQ consists of 16 items which are categorized into four namely: Overall Satisfaction (OVERALL), System Usability (SYSUSE), Information Quality (INFOQUAL) and Interface Quality (INTERQUAL). The results obtained in this study are the SYSUSE category is 3.27, the value of the INFOQUAL category is 3.37, the value of the INTQUAL category is 3.40 and the value of the OVERALL category is 3.18.